*Una investigación en historia de la traducción: cuatro traductores colombianos del siglo XIX - Montoya, Paula; Ramírez, Juan Guillermo; Ángel, Claudia (Íkala, Revista de Lenguaje y Cultura, 2006)
In this article, we review a research project in translation history which focuses on the production of four Colombian translators who lived in the second half of the 19th Century. In order to establish the theoretical framework of this project, some of the fundamentals of research in translation history are reviewed, basically those developed by Gideon Toury, Anthony Pym and Antoine Berman. Received: 31-03-06 / Accepted: 03-08-06 How to reference this article: Montoya, P.; Ramírez, J. G. & Ángel, C. (2006). Una investigación en historia de la traducción: cuatro traductores colombianos del siglo XIX. Íkala. 11 (1), pp. 13 – 30